AN ANALYSIS OF CLASSROOM INTERACTION TO DEVELOP STUDENTS’ SPEAKING ABILITY IN SMPN SATAP 3 CINA - Asilah, Nur; Atmowardoyo, Haryanto; Muhayyang, Maemuna (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research aims to find out(1) the type of classroom interaction used by teacher in developing students’ speaking ability, and (2) types of classroom interaction affect the students’ speaking ability.This research uses qualitative methods by using 3 research instruments, namely, observation, documentation, and interview, this research was conducted on teacher and grade 8 students at SMPN Satap 3 Cina. This research used purposive sampling by selecting 10 students based on the results of the highest to lowest English learning scores. The results of the analysis of this study indicate that the type of classroom interaction used by teacher to develop students' speaking abilities, namely collaborative learning, discussion, interactive sessions, telling, reading with a loud voice, and role play. Of the six types of classroom interaction used by the teacher, all students who were interviewed said that the types of classroom interaction that can improve students' speaking skills are collaborative learning, discussion, and role-play. As for the interactive session, telling, and reading with a loud voice type of class interaction, most students think that this type of class interaction has not been able to improve their speaking ability because some students are still nervous, feel embarrassed, and still lack vocabulary. This is also confirmed by the teacher, apart from that lack of learning media in schools. Based on this, it can be concluded that students’ speaking abilities affect to increase through classroom interactions used by teacher to students, including grammar, fluency, vocabulary, comprehension, and chronological age. Keywords: Class Interaction; Speaking Ability